2017
DOI: 10.1080/15685551.2017.1398208
|View full text |Cite
|
Sign up to set email alerts
|

Modified polyether-sulfone membrane: a mini review

Abstract: Polyethersulfone has been widely used as a promising material in medical applications and waste-treatment membranes since it provides excellent mechanical and thermal properties. Hydrophobicity of polyethersulfone is considered one main disadvantage of using this material because hydrophobic surface causes biofouling effects to the membrane which is always thought to be a serious limitation to the use of polyethersulfone in membrane technology. Chemical modification to the material is a promising solution to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(76 citation statements)
references
References 69 publications
2
67
0
Order By: Relevance
“…This conclusion was based on the observation that accumulation of oxyanions was not affected by the fouling layer whereas accumulation of cations was significantly reduced. Alenazi et al (2017) argued that the hydrophobic nature of PES makes this polymer more sensitive to biofilm development, and proposed an increase in the hydrophilicity of the membrane surface to reduce its sensitivity to fouling. Harman et al (2009) observed a 1.5‐fold increase in alkylphenol accumulation by POCIS as a result of biofouling.…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion was based on the observation that accumulation of oxyanions was not affected by the fouling layer whereas accumulation of cations was significantly reduced. Alenazi et al (2017) argued that the hydrophobic nature of PES makes this polymer more sensitive to biofilm development, and proposed an increase in the hydrophilicity of the membrane surface to reduce its sensitivity to fouling. Harman et al (2009) observed a 1.5‐fold increase in alkylphenol accumulation by POCIS as a result of biofouling.…”
Section: Resultsmentioning
confidence: 99%
“…To measure the maximum moisture content that can be absorbed by a membrane, water retention analysis of the pure PES and hybrid membranes was carried out. The lowest water retention capacity (55%) was observed for the pure PES membrane among all membranes, which can be attributed to the hydrophobic character of the PES membrane [31]. The CT-PES membrane had the highest water retention capacities (70%) due to the presence of a polar phenol group in cannabinoids [15,16,21] that make the membranes relatively more hydrophilic, thus allowing water to pass through it.…”
Section: Mechanical Testingmentioning
confidence: 94%
“…In contrast to other commonly applied polymers such as polysulfone (PSf), cellulose acetate (CA), polyvinylidene fluoride (PVDF), or polyamide (PA), it stands out due to particular characteristics. The favoring properties of PES include a high glass transition temperature of 225 °C, a large chemical, mechanical, and thermal resistance, an excellent biocompatibility, as well as the potential application within a large pH range . Furthermore, the use of PES enables an easy fabrication of membranes with a large range of different pore sizes, which can be applied in several different modules and configurations .…”
Section: Introductionmentioning
confidence: 99%